ANALISIS PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY PADA PERBANKAN SYARIAH DALAM PRESPEKTIF SHARIAH ENTERPRISE THEORY (STUDI KASUS PADA LAPORAN TAHUNAN PT BANK SYARIAH MANDIRI TAHUN 2015 DI BURSA EFEK INDONESIA) - Lubis, Nurhayani; Hardi, Hardi; Aznuriyandi, Aznuriyandi; Fradila, Intan (Jurnal Daya Saing, 2018)
Abstract :This research was conducted to describe and analyze the implementation of how much Corporate Social Responsibility is in Mandiri Syariah Banking in Pekanbaru. This study uses descriptive qualitative research method using Bank Syariah Mandiri annual report data in 2015. To analyze the data properly, accurate, reliable and systematic data is needed so that the results obtained can describe objects that are being researched correctly through literature study on Shariah Enterprise Theory and field studies in the form of in depth interviews. The results show that Bank Mandiri Syariah in 2015 has implemented Corporate Social Responsibility well, in terms of the Shariah Enterprise Theory it can be seen that Bank Mandiri Syariah is committed to carrying out its social responsibility well.